1999
DOI: 10.1002/(sici)1520-6343(1999)5:4<219::aid-bspy2>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Infrared spectroscopy of human tissue. V. Infrared spectroscopic studies of myeloid leukemia (ML‐1) cells at different phases of the cell cycle

Abstract: Infrared spectra of myeloid leukemia (ML-1) cells are reported for cells derived from an asynchronous, exponentially growing culture, as well as for cells that were fractionated according to their stage within the cell division cycle. The observed results suggest that the cells' DNA is detectable by infrared spectroscopy mainly when the cell is in the S phase, during the replication of DNA. In the G1 and G2 phases, the DNA is so tightly packed in the nucleus that it appears opaque to infrared radiation. Conseq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
91
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(101 citation statements)
references
References 14 publications
10
91
0
Order By: Relevance
“…However, individual cell spectra show large spectral variations, both for cultured cells and cells exfoliated from human donors. Spectral variations observed for cultured cells have been the subject of studies in the authors' laboratory for about 7 years, and have been attributed to different stages in the cell division cycle [1][2][3][4]. However, we also observe large spectral heterogeneity in exfoliated epithelial cells, which should be divisionally inactive, and relatively homogeneous.…”
Section: Introductionmentioning
confidence: 55%
“…However, individual cell spectra show large spectral variations, both for cultured cells and cells exfoliated from human donors. Spectral variations observed for cultured cells have been the subject of studies in the authors' laboratory for about 7 years, and have been attributed to different stages in the cell division cycle [1][2][3][4]. However, we also observe large spectral heterogeneity in exfoliated epithelial cells, which should be divisionally inactive, and relatively homogeneous.…”
Section: Introductionmentioning
confidence: 55%
“…As the results show, a good differentiation of the two cell types can be achieved with both techniques, indicating the feasibility of cell typing by both vibrational spectroscopy methods with particular emphasis on the Raman results. As it has been mentioned earlier, several FTIR studies [16][17][18][19][20][21][22][23] have been reported in cell type discrimination but there have been only few studies on the Raman spectroscopic approach. 24 When the loadings plots were inspected (data not shown here), the first component could be assigned to a mean spectrum.…”
Section: Resultsmentioning
confidence: 99%
“…Several successful Fourier transform infrared (FTIR) studies for discrimination of Pap smear and other exfoliated cells have been reported. [16][17][18][19][20] Studies on apoptosis and identification of MDR and sensitive phenotypes in a cell line have also been described, [21][22][23][24] showing the potentials and applications of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, studies to methodically assess this variability have been limited to investigating cultured cell lines [49] or cells that can be isolated from peripheral blood [36]. The combination of FTIR microscopy with multivariate image processing provides a direct method to assess biological variability and thereby add to the discriminating power of any diagnostic algorithm.…”
Section: Discussionmentioning
confidence: 99%